Three new species of Laonice (Annelida: Spionidae) from the NE Atlantic and Mediterranean Sea - Sikorski, Andrey V.; Ravara, Ascensão; Pavlova, Lyudmila V.; Lampadariou, Nikolaos; Cunha, Marina R. (Zootaxa, 2026)
The study of newly available specimens belonging to genus Laonice (Annelida: Spionidae) from six different localities in the NE Atlantic Ocean and E Mediterranean Sea allowed the description of three new species, L. gadirensis sp. nov., L. kithirensis sp. nov., and L. moroccensis sp. nov., all three belonging to subgenus Sarsiana. Based on the new data the status of one morphological species group formerly included in subgenus Sarsiana is raised to the subgeneric rank as Wubaolingia Sikorski subgen. nov., allowing a clearer defined diagnosis of subgenus Sarsiana. Moreover, it is suggested that within subgenus Sarsiana the degree of fusion between prostomium and peristomium may vary from a barely noticeable membrane hidden in the fold between the two to a complete fusion along the anterior edges, while a similar variation in the fusion of prostomium and peristomium is also to be expected within subgenus Laonice, according to the discussion concerning the species L. praecirrata. Subgenus Appelloefia needs also to be redefined due to the possible heterogeneity within the group.